2013
DOI: 10.1245/s10434-013-3208-y
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Gastrectomy After Intravenous and Intraperitoneal Paclitaxel (PTX) Administration with Oral S-1 for Peritoneal Dissemination of Advanced Gastric Cancer with Malignant Ascites

Abstract: Salvage gastrectomy after chemotherapy of S-1 with IV and IP PTX is promising, even for patients with highly advanced gastric cancer and severe peritoneal metastasis and malignant ascites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 29 publications
0
59
0
Order By: Relevance
“…Another effort to use neoadjuvant intraperitoneal chemotherapy to control peritoneal metastases prior to gastrectomy was presented by Kitayama et al [59] . They used a combination of intraperitoneal and intravenous paclitaxel along with S-1.…”
Section: Results After Nipsmentioning
confidence: 99%
“…Another effort to use neoadjuvant intraperitoneal chemotherapy to control peritoneal metastases prior to gastrectomy was presented by Kitayama et al [59] . They used a combination of intraperitoneal and intravenous paclitaxel along with S-1.…”
Section: Results After Nipsmentioning
confidence: 99%
“…Other strategies for normothermic intraperitoneal chemotherapy long term for gastric cancer with peritoneal metastases Another approach to the concept of NIPEC-LT has been reported by Kitayama and colleagues [27]. They used oral S1 combined with intraperitoneal paclitaxel (20 Yet another approach to NIPEC-LT was reported by Fujiwara and coworkers [29].…”
Section: Results After Nipec-lt Plus Gastrectomy With Cytoreductionmentioning
confidence: 99%
“…Thus far, PTX is considered to be the most suitable drug for IP chemotherapy, due to its prolonged retention time. In fact, recent clinical studies have suggested the usefulness of IP-PTX for peritoneal lesions in ovarian [36] or gastric [11,37] cancers. However, it remains unclear how deep the IP-PTX actually infiltrates into a tumor nodule on the peritoneal surface in these patients.…”
Section: Discussionmentioning
confidence: 99%